Designing an ICT Service Chatbot at the Global Institute - Firgiawan, Annis; Asy'ari, Hasan; Susanto, Fredy; Bangun, Eka Uliyanti Putri Br (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2024)
The design of an ICT service chatbot at Global Institute aims to enhance the efficiency and effectiveness of providing technical support to users, including staff, lecturers, and students. With the increasing demand for Information and Communication Technology (ICT) services, a solution is needed that can provide quick and accurate responses to various technical issues. This chatbot is designed using artificial intelligence (AI) technology that enables natural interaction with users through a conversational platform. The main features implemented in the chatbot include managing technical support requests, automatically resolving common issues, and providing guidance on the use of ICT devices and applications. This research employs an object-oriented development methodology and incorporates an Agile approach to ensure flexibility and responsiveness in development. System trials were conducted involving end users to gather feedback and make necessary improvements. The test results show that the chatbot significantly reduces response time and the workload of the ICT team, as well as improves user satisfaction. Thus, the implementation of this chatbot is expected to positively contribute to the quality of ICT services at Global Institute.